MID-TERM STIMULI, BASIC PRINCIPLES, AND READJUSTMENTS: AMERICA IN CENTRAL ASIA - BAFOEV, Feruz (CENTRAL ASIA AND THE CAUCASUS, 2015)
The United States is kept busy by the events unfolding worldwide and on the Eurasian continent (the Ukrainian crisis, Afghanistan, the anti-Russian sanctions, oil and gas prices, the Muhammad cartoons crisis, the Lausanne talks on the Iranian nuclear file, etc.). Under the pressure of these and many other factors, Washington is actively readjusting its Central Asian policy, as well as its conceptual approaches to the regional policies of other players and to the changing specifics of each of the Central Asian countries.Its claims to regional leadership are challenged by the Color Revolutions and its ambiguous involvement in the Middle East. Hence the tectonic shifts in the minds of the Central Asian elites, the dampened Pro Western enthusiasm, and the noticeable changes in public opinion in the Central Asian republics.The author has discussed America’s foreign policy and its implementation in the region based on the values the United States declares to be fundamental, the specifics of the “progress of democracy,” and the new real and potential regional security risks. Possible steps by other players involved in the region—China, Russia, Turkey, and Iran—and America’s possible response to potential developments are also discussed. The author looks at the relations between the U.S. and each of the CentralAsian republics. When analyzing the relationship between Washington and Astana, Tashkent, Ashghabad, Dushanbe, and Bishkek, he concentrates on synergetic methods, which presuppose the quest for and use of active constructive impacts on unstable situations.